Reproductive Behaviour and Semen Characteristics of Exotic Rams under Temperate Conditions of Kashmir - ISLAM, R; KHAN, M Z; WANI, G M; GANAIE, T A S (The Indian Journal of Animal Reproduction, 2023)
Rams with sound reproductive health were selected from Corriedale, Polled Dorset and Hampshirebreeds at University Sheep Research Station, Shuhama, Srinagar. Sexual behaviour like sniffing, kickingwith fore legs, moving tongue in and out, courting grunt, Flehmen response, number of mounts requiredper collection and reaction time to I st mount were studied. Semen was collected with artificial vagina (AV) •using non-estrous ewe as dummy. The ejaculate was examined visually for volume, colour andconsistency. Microscopic examination of semen was done for mass activity (0 t,, 4 scales), initial motilityPercentage, spermatozoa concentration, live sperm count and percent intact acro!
Keywords: Rams; Corriedale; Polled Dorset; Hampshire; Reproductive behaviour; Ejaculate; Immediate extension; Semen quality